2007
DOI: 10.1093/cercor/bhl167
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity for Animal Vocalizations in the Human Auditory Cortex

Abstract: We aimed at testing the cortical representation of complex natural sounds within auditory cortex using human functional magnetic resonance imaging (fMRI). To this end, we employed 2 different paradigms in the same subjects: a block-design experiment was to provide a localization of areas involved in the processing of animal vocalizations, whereas an event-related fMRI adaptation experiment was to characterize the representation of animal vocalizations in the auditory cortex. During the first experiment, we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 74 publications
8
58
2
Order By: Relevance
“…the supratemporal N1 generator), which should cause frontocentrally maximal effects. This is in line with Altmann et al (2007) who proposed a processing of animal vocalizations in putatively nonprimary auditory areas of the superior temporal gyrus (cf. also Lewis et al, 2004).…”
Section: Overall Processing Differences Between the Familiar And The supporting
confidence: 91%
See 2 more Smart Citations
“…the supratemporal N1 generator), which should cause frontocentrally maximal effects. This is in line with Altmann et al (2007) who proposed a processing of animal vocalizations in putatively nonprimary auditory areas of the superior temporal gyrus (cf. also Lewis et al, 2004).…”
Section: Overall Processing Differences Between the Familiar And The supporting
confidence: 91%
“…also Lewis et al, 2004). Whereas Altmann et al (2007) as well as Lewis et al (2004) further reported a left-hemispheric predominance in the processing of animal sounds or familiar environmental sounds in fMRI data, no lateralization effects were observed in the present study. The posterior distribution of the N1 familiarity effect could reflect the activation of additional cortical generator structures for a familiar environmental sound (for example, the anterior-temporal cortex that has been proposed to be critical for the activation of semantic knowledge representations; cf.…”
Section: Overall Processing Differences Between the Familiar And The contrasting
confidence: 62%
See 1 more Smart Citation
“…Participants were then asked to identify these vocalizations as being either from a human or from a nonhuman animal. No previous research to our knowledge has examined judgments of whether stimuli were produced by human or nonhuman animals, but neuroimaging work has examined cerebral responses to nonhuman animal vocalizations relative to a variety of other stimuli including human voices (e.g., Lewis, Brefczynski, Phinney, Janik, & DeYoe, 2005;Altmann, Doehrmann, & Kaiser, 2007;Belin et al, 2008). De Lucia, Clarke, andMurray (2010) found that human and nonhuman animal vocalizations elicited early responses in statistically indistinguishable brain networks.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand highly periodic sounds with inharmonic spectra generally reflect machinery [32] and water sounds are characterized by slowly modulated broadband noises, often saturated with transient components [27]. There is neurophysiological evidence that sounds generated by tools are processed by distinct cortical pathways from animal vocalizations, which excited similar pathways to human speech [33,34], implying this important distinction in source properties is preserved well into the cortex.…”
Section: Environmental Sounds and Listening In The Worldmentioning
confidence: 99%